Proliferative diabetic retinopathy in unsuspected diabetes mellitus: a case report (Ukrainian Journal of Ophthalmology, 2025)
Introduction. According to World Health Organization, nowadays, the amount of diabetic patients has exceeded 1,000 million people, equaling 3% of the Earth population. Unsuspected diabetes mellitus is a disease in a latent form without acute symptomatology.Purpose. To determine the etiology of retinopathy in the patients applied to the Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine. Material and Methods. Seven patients underwent the treatment at Department for Inflammatory Eye Diseases in the Filatov Institute of Eye Diseases and Tissue Therapy. The patients complained of both distance and near visual loss. All patients were diagnosed proliferative DRP with neovascularization, hemorrhage, and exudates. Blood glucose tests were within normal ranges and did not exceed 5.8 mmol/l. In the course of the treatment, visual acuity improved by three lines, at an average.Conclusion. As a result of ophthalmic examination, ophthalmic diagnosis, and, afterwards, endocrinological examination, all patients were diagnosed diabetes mellitus in a latent form.
Keywords: diabetes mellitus; unsuspected diabetes; latent diabetes; diabetic retinopathy